Leading Change in Organisations: A Focus on Quality Management - Randeree, K (Common Ground, 2008)
In contemporary knowledge driven economies, local organisations must aim to be competitive, in part, through ensuring the delivery of high quality in their goods and services. Changes in the social environment where customers are more mature and better informed have forced these organisations to consider alternatives to traditional methods of running their business. Consequently, Total Quality Management (TQM) has attracted the attention of many organisations as a potential system to improving their competitiveness and efficiency. Implementation of a TQM system necessitates transformation away from conventional ways of delivering business objectives by changing the way in which people deal with internal or external work processes. TQM looks at change within the organisation as an inevitable process which should be managed flawlessly. Unfortunately, TQM initiatives often fail when implementation begins, with the proportion of successes in TQM implementation only within the range of 20 to 35 per cent, according to Brown (1992 cited in Redman & Grieves 1999). The reasons for failure were associated with the problem of sustainability of leadership and purpose, absence of strategic communications and teamwork for quality improvement and the lack of total commitment to the TQM philosophy and practice. These were attributed to poor understanding of the TQM philosophy by senior management and a lack of employee opportunities to relate training activities with company vision. This paper thus evaluates the dynamics of organisation change with a view to understanding causes of success and failure. The research aims to review earlier studies and, through the results of those studies, analyse the role TQM plays in organisational change management.